Effect of colchicine and oryzalin treatment on polyploid induction and morphogenesis of Anoectochilus setaceus Blume cultured in vitro - Quoc Luan, Vu; Thuy Tam, Do Thi; Phuc Huy, Nguyen; Thanh Tung, Hoang; Hien, Vu Thi; Manh Cuong, Do; The Vinh, Bui Van; Tan Nhut, Duong (Vietnam Journal of Biotechnology, 2020)
Jewel orchid (Anoectochilus setaceus Blume) is one of the important medicinal plants used for many common diseases treatment such as hypertension, diabetes, and heart, liver and lung diseases, as well as  improving the health in general. Polyploid induction using colchicine and oryzalin has been widely performed in various types of crops and could be considered a valuable tool for plant breeding. In the present study, in vitro young shoots of A. setaceus Blume (1 cm in height) were treated with different concentrations of colchicine (0, 1, 2, 4, 6, 8, and 10 µM) and oryzalin (0, 10, 20, 40, 60, 80, and 100 µM) at different durations (0, 12, 24, 36, and 48 h). The results showed that shoots with length of treatment from 24 to 48 h and the concentrations from 2 to 10 µM of colchicine and from 40 to 100 µM of oryzalin appeared morphological differences (10.00% - 16.00%) but the tendency to return to normal of these shoots after several times of sub-culture was observed. Stomatal length had a close correlation with the level of ploidy. Diploid plantlets (2n = 2x) had the average stomatal length of 33.50 µm when observed under an optical microscope at 100x magnification and corresponding to the peak at 70 FL in flow cytometric DNA histogram. In all identified polyploid plantlets, the stomatal lengths were greater than 40.12 µm. Moreover, flow cytometric analysis indicated that plantlets with stomatal lengths ranged from 40.12 to 50.00 µm were diploid-tetraploid mosaicisms represented by two separate peaks at 70 FL and 90 FL. Finally, samples treated with 4, 6, and 8 µM colchicine with treatment time of 48 h, and 60 µM oryzalin with treatment time of 24 h that had stomatal lengths ranged from 52.03 to 71.25 µm were determined to be tetraploid (2n = 4x) represented by a peak at 120 FL position.